2020
DOI: 10.3389/fpls.2019.01655
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Rapid Radiations With Targeted Sequencing

Abstract: be merged for downstream analyses. Moreover, our study contributes to the growing consensus that targeted sequencing data are a powerful tool in resolving rapid radiations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 86 publications
6
130
1
Order By: Relevance
“…Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones. While we do not compare these alternative probes, the results from our study, Larridon et al (2020) and Murphy et al (2020) suggest that an appropriately designed universal probe set can capture adequate phylogenomic information to resolve relationships at the species-level and even at the population-level (Van Andel et al, 2019). Liu et al (2019) showed experimentally that when probes are <30% divergent from regions targeted, enrichment worked adequately (see Figure 6 and Supplementary Figure S6 in Liu et al, 2019).…”
Section: Efficacy Of Universal Probesmentioning
confidence: 80%
See 2 more Smart Citations
“…Whereas Kadlec et al (2017) argued that high sequence variability across angiosperm orders precluded the usefulness of universal probes in resolving species-level relationships, Chau et al (2018) found that general purpose probes can be as effective as taxon-specific ones. While we do not compare these alternative probes, the results from our study, Larridon et al (2020) and Murphy et al (2020) suggest that an appropriately designed universal probe set can capture adequate phylogenomic information to resolve relationships at the species-level and even at the population-level (Van Andel et al, 2019). Liu et al (2019) showed experimentally that when probes are <30% divergent from regions targeted, enrichment worked adequately (see Figure 6 and Supplementary Figure S6 in Liu et al, 2019).…”
Section: Efficacy Of Universal Probesmentioning
confidence: 80%
“…To date, other than in Schefflera, the Angiosperms-353 enrichment panel (Johnson et al, 2018) has only been tested at the species level in sedges (Cyperus; Larridon et al, 2020) and Old World pitcher plants (Nepenthes; Murphy et al, 2020) and at the population level (SNPs) in rice (Oryza; Van Andel et al, 2019). When comparing data matrices containing on-target loci only, both Larridon et al (2020) and Murphy et al (2020) had a higher capture success (Table 3); an expected result since they worked with a greater proportion of silica-dried tissue (Brewer et al, 2019). However, their mean P PIC was lower than ours (Table 3), probably as a result of our filtering approach, which combined two custom scripts -max_overlap (representativeness x completeness x evenness) and optrimAl (per locus gap threshold optimization) -to increase signal while reducing missing data in our data matrixes.…”
Section: Efficacy Of Universal Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CTAB protocol can be easily modified to suit different tissue types and ages, regardless of preservation strategies, and upscaled to process 96–192 samples at a time (see Dryad repository associated with Beck et al., , b; and supplementary materials for Larridon et al., ) with a Geno/Grinder. For dried and old herbarium materials, higher concentrations of β‐mercaptoethanol (i.e., 0.4%) are recommended in the CTAB step, a fast vortex and clean‐up with chloroform : isoamyl alcohol, and long incubations in isopropanol at −20°C (e.g., 48 h, or even up to a week for precious and difficult materials; Larridon et al., ). Phenol cleaning is highly recommended in plant DNA isolation protocols (Drábková et al., ), but high DNA concentrations can be achieved without it.…”
Section: Dna Extractionmentioning
confidence: 99%
“…The accessions available for phylogenetic studies in natural history collections are essential to survey the diversity of species-rich groups, to include narrow endemics difficult to collect in the field and to account for variation in widespread and polymorphic species (Särkinen et al, 2012;Buerki and Baker, 2016;Bieker and Martin, 2018;Valderrama et al, 2018). The use of target enrichment strategies to gather low or single copy nuclear loci for phylogenomics of plant lineages at different scales (Nicholls et al, 2015;Sass et al, 2016) is becoming a standard technique, and the establishment of universal probe sets could reduce costs and time while enabling the merging of datasets from different studies and across plant lineages (Johnson et al, 2019;Larridon et al, 2020). However, divergence between the target sequences and the baits does affect capture efficiency (Larridon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%